The impact of climatic elements on the design of residential units in the city of Baqubah (Journal of the College of Basic Education, 2024)
The objective of the current research is to study the effect of climatic elements on the design of housing units in Baquba city, especially as these elements directly affect the comfort of the human inside the housing units. As a place where the person is comfortable, the research relied on the descriptive analytical method as well as the questionnaire form (190) housing units from all districts of the city of Baquba ( 21 ), including the research on two topics in addition to the theoretical framework and conclusions, recommendations and list of sources, and the research reached several conclusions, the most important, the study area receives large amounts of solar radiation, High temperatures inside the housing units, it turns out that a large proportion of housing units contain from (5-10) window, and that a large proportion of housing units took advantage of all the actual area of ​​land in the building, which was reflected in the high heat of the d Rajat these units